2012
DOI: 10.2340/00015555-1170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silver-based Wound Dressings on the Bacterial Flora in Chronic Leg Ulcers and Its Susceptibility In Vitro to Silver

Abstract: Silver-based dressings have been used extensively in wound management in recent years, but data on their antimicrobial activity in the clinical setting are limited. In order to explore their effects on chronic leg ulcer flora, 14 ulcers were cultured after at least 3 weeks treatment with Aquacel Ag(®) or Acticoat(®). Phenotypic and genetic silver resistance were investigated in a total of 56 isolates. Silver-based dressings had a limited effect on primary wound pathogens, which were present in 79% of the cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 29 publications
4
62
1
Order By: Relevance
“…Our findings are also similar to those published by Lara et al 14 in the United States, which recognized the antibacterial and antiviral potential of SNC, as well as those findings by Murphy and Evans 15 also in the United States, who found that SNC have better antibiotic effect than SSD, especially against particular microorganisms. Furthermore, the data presented in this study are similar to Mohajeri-Tehran et al 16 in Iran; these investigators found evidence of antibiotic effect from SNC in patients with diabetic foot ulcers; Sütterlin et al 17 in Sweden concluded that the compounds based on silver, including SNC and SSD, are useful in neither eradicating microorganisms that colonize chronic wounds nor in preventing colonization of them. Other studies have also proved that the antibiotic effect of silver-based compounds is due to their good penetration into tissues, their safety and decreased healing time, as well as the low rate of microbial resistance related to them; however, regarding safety, some rare cases of hepatotoxicity and skin lesions have been reported.…”
supporting
confidence: 77%
“…Our findings are also similar to those published by Lara et al 14 in the United States, which recognized the antibacterial and antiviral potential of SNC, as well as those findings by Murphy and Evans 15 also in the United States, who found that SNC have better antibiotic effect than SSD, especially against particular microorganisms. Furthermore, the data presented in this study are similar to Mohajeri-Tehran et al 16 in Iran; these investigators found evidence of antibiotic effect from SNC in patients with diabetic foot ulcers; Sütterlin et al 17 in Sweden concluded that the compounds based on silver, including SNC and SSD, are useful in neither eradicating microorganisms that colonize chronic wounds nor in preventing colonization of them. Other studies have also proved that the antibiotic effect of silver-based compounds is due to their good penetration into tissues, their safety and decreased healing time, as well as the low rate of microbial resistance related to them; however, regarding safety, some rare cases of hepatotoxicity and skin lesions have been reported.…”
supporting
confidence: 77%
“…In contrast to silver (Sütterlin et al, 2012), no bacterial resistance against PHMB has been described yet (Wessels & Ingmer, 2013). Additionally, it is stated to be 'practically non-toxic', well tolerated on skin, eyes, nose, ciliated epithelium and wounds, and showed no sensitizing or photosensitizing effects in animal tests (reviewed by Hubner & Kramer 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ag-coated bandages are used to cover burns and traumatic injuries. Silver-impregnated polymers are commonly used in medical devices such as catheters to prevent the formation of bacterial biofilms (7,43). Besides these and other medical applications, silver compounds are employed in a variety of nonmedical products.…”
Section: Discussionmentioning
confidence: 99%